1996
DOI: 10.1073/pnas.93.7.2759
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of poly(alpha2,8-deaminoneuraminic acid) in mammalian tissues: widespread and developmentally regulated but highly selective expression on glycoproteins.

Abstract: In tissues of higher organisms homopoly-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…In mammals, KDN was first identified in various tissues including human lung carcinoma cells but at a much lower abundances than Neu5Ac (4) and was subsequently found on human red blood cells and ovarian cancer cells (5). The development of linkage-specific KDN antibodies (6,7) has allowed the identification of ␣2,8-linked polyKDN in many mammalian tissues (8), including the human lung (9).…”
mentioning
confidence: 99%
“…In mammals, KDN was first identified in various tissues including human lung carcinoma cells but at a much lower abundances than Neu5Ac (4) and was subsequently found on human red blood cells and ovarian cancer cells (5). The development of linkage-specific KDN antibodies (6,7) has allowed the identification of ␣2,8-linked polyKDN in many mammalian tissues (8), including the human lung (9).…”
mentioning
confidence: 99%
“…Following the first report of KDN in 1986 (1), its association with a diverse number of living organisms ranging from bacterial capsular polysaccharide (2) to animal glycoproteins and glycolipids (3)(4)(5)(6)(7)(8)(9)(10)(11) has been demonstrated. Interestingly, immunochemical techniques suggested the presence of an oligomeric form of ␣238-linked KDN in mammalian tissues (10,11), and the occurrence of KDN residues was confirmed by biochemical and chemical methods (12). A unique feature of KDN-containing glycoconjugates is their complete resistance to the action of the known bacterial and viral exosialidases (1,5,9,13).…”
mentioning
confidence: 99%
“…and a2!8-linked oligoKDN, respectively [50,51]. The two useful reagents, mAb.kdn8kdn and KDNase Sm, were used in our collaborating studies for immunohistochemical detection of a2!8-linked oligoKDN epitopes in different organs of rat [51,52]. The results obtained were the ®rst indication of the presence of KDN residues in mammalian tissues.…”
Section: Evidence For the Occurrence Of Kdn And Kdn Residues In Mammalsmentioning
confidence: 99%
“…Because, in our previous study [30,52], KDN was shown to be expressed in all of human lung cancer cell lines examined, we initiated a systematic survey of KDN in white blood cells, blood plasma, ascites uid, and ascites cells of patients of different types of cancer. The objectives of these studies are two-fold: one is to develop a possible utilization of levels of KDN as a reliable and useful method for monitoring Diversity in sialic and polysialic acid residues 795 q1999 IUPAC, Pure Appl.…”
Section: Evidence For the Occurrence Of Kdn And Kdn Residues In Mammalsmentioning
confidence: 99%